2021
DOI: 10.1155/2021/6096017
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Hyperreflective Foci as an Optical Coherence Tomography Biomarker in Retinal Diseases: Characterization and Clinical Implications

Abstract: Hyperreflective foci (HRF) is a term coined to depict hyperreflective dots or roundish lesions within retinal layers visualized through optical coherence tomography (OCT). Histopathological correlates of HRF are not univocal, spacing from migrating retinal pigment epithelium cells, lipid-laden macrophages, microglial cells, and extravasated proteinaceous or lipid material. Despite this, HRF can be considered OCT biomarkers for disease progression, treatment response, and prognosis in several retinal diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 121 publications
1
33
0
Order By: Relevance
“…As a major OCT feature discussed in the current paper, retinal HRF can be seen in multiple retinal diseases, and serves as a promising but controversial OCT biomarker in DME treatment Theories have been expounded upon the pathophysiology of HRF, including lipoprotein extravasation [18], inflammationinduced microglial cell activation [19], migrating retinal pigment epithelium (RPE) cells [58], and degenerated photoreceptor cells [59], etc. It is accepted that HRF is related to retinal inflammation in DME [57], and HRF is a potential biomarker for DME treatment management. Compared to anti-VEGF, corticosteroid treatment caused more HRF reduction in DME eyes [60].…”
Section: Discussionmentioning
confidence: 99%
“…As a major OCT feature discussed in the current paper, retinal HRF can be seen in multiple retinal diseases, and serves as a promising but controversial OCT biomarker in DME treatment Theories have been expounded upon the pathophysiology of HRF, including lipoprotein extravasation [18], inflammationinduced microglial cell activation [19], migrating retinal pigment epithelium (RPE) cells [58], and degenerated photoreceptor cells [59], etc. It is accepted that HRF is related to retinal inflammation in DME [57], and HRF is a potential biomarker for DME treatment management. Compared to anti-VEGF, corticosteroid treatment caused more HRF reduction in DME eyes [60].…”
Section: Discussionmentioning
confidence: 99%
“…There are several hypotheses explaining the origin of HRF in general. Some studies suppose that the HRF represents an inflammatory component like microglia or migrated RPE and/or the extravasation of lipoproteins following the breakdown of the blood-retinal barrier [ 53 , 54 ]. It has been shown that HRF foci are also a predictive marker of the final visual outcome in diseases like retinal vein occlusion [ 50 ], diabetic retinopathy [ 46 ], polypoidal choroidal vasculopathy [ 55 ], neovascular age-related macular degeneration [ 55 ], but also in degenerative diseases like RP [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperreflective foci (HRF) are visualized at any retinal layer through spectral-domain/swept-source optical coherence tomography (SD/SS-OCT) in several retinal diseases and are defined as well-demarcated lesions with equal reflectivity to the RPE bands. They are sometimes detected as hyperpigmentation on color fundus photography 2 . They are believed to migrate toward the vitreous side of the retina from the RPE in eyes with early/intermediate AMD.…”
Section: Introductionmentioning
confidence: 99%